Performance of wheat under poplar (Populus deltoides 8artr. ex Marsh) based agroforestry system - Pal, Mahender; Panwar, G.S.; Dhanai, C.S.; Anand, K.B. (Indian Journal of Agroforestry, 2020)
The performance of eight wheat varieties namely, HO-2329, WH-542, PBW-373, PBW-222, Raj-3765, UP- 2338, HO-2687 and PBW-34 was assessed under six year old poplar (G-48) plants spaced at 5 X 4m. The results revealed that VarietyWH-542 recorded highest values for number of shoots per square meter (120), plant height (85.22 cm.), leaf dry weight (88.80 g/m2) and LeafArea Index (1.96). However, minimum number of shoots per square meter was observed in HO-2687 (101/m2). Grain weight per spike was obtained maximum with PBW 373 (1.49 g./ spike) followed by WH-542. Maximumgrain yield ofWH-542 (29.35 q/ha) followed by 27.88 q/ha, 24.62 q/ha, and 23.43 q/ha with PBW-373, HO2329 and HO2687, respectively. On the basis of the findings of present investigation, variety WH-542, PBW-373 and HO-2329were found most suitable for cultivation under sub-optimum growth conditions i.e., under shelterbelts of poplar.